Research progress on the molecular basis of plant-Ralstonia solanacearum recognition - XIAO Zhiliang; YANG Aiguo; ZHANG Meixiang (浙江大学学报. 农业与生命科学版)
Ralstonia solanacearum causes bacterial wilt disease in multiple crops, which severely threatens the global crop safety production. This pathogen exhibits high genetic diversity and evolves rapidly, and there is a lack of effective disease-resistant varieties in production, which brings great challenges for effective disease control. Identifying receptor proteins in plants that recognize associated molecular patterns or effectors of R. solanacearum and elucidating their molecular recognition mechanisms can provide clues to understand the mechanisms of plant-pathogen interaction, and lay a basis for the development of broad-spectrum disease resistance in plants. This paper reviewed the recent progress on the molecular basis of plant-R. solanacearum recognition. We mainly focused on the identification and functional analysis of membrane and intracellular receptors that recognize R. solanacearum in plants, as well as the mechanism behind receptor recognition of the associated molecular patterns or effectors from R. solanacearum. Besides, we provide research prospects for the exploration and utilization of disease-resistant resources against R. solanacearum in the future.